Study on Cytochrome P450 Family 1 B1 Gene Mutations in Primary Congenital Glaucoma Affected Egyptian Patients - Amanne Feisal Esmael; Hanaa Abdel-Sadek Oraby; Soheir Mohamed El Nahas (Highlights on Medicine and Medical Research Vol. 1, 2021)
Aims: Primary congenital glaucoma (PCG) is a leading cause of childhood blindness. Primary congenital glaucoma manifests in early infancy and is characterized by an elevated IOP, large cornea, and Haab’s striae. Variable degrees of corneal haze, photophobia, epiphora, and blepharospasm are also seen. The cytochrome P450 family 1, subfamily B, polypeptide 1 (CYP1B1) is the most mutated gene that is associated with PCG. Very few studies have examined the promoter region and exon1 of the CYP1B1 gene. This work was planned to contribute to the description of the possible causative mutations of CYP1B1 gene that are related to PCG affected Egyptian patients. Patients and Methods: Patients diagnosed as glaucomatous based on their symptoms and detailed ophthalmological examinations at the time of presentation, underwent an intraocular pressure lowering surgical procedure. Investigations were further proceeded on the molecular level. Sequencing-based mutation screen for the promoter region, exon1 and the coding region of exon3 of CYP1B1 gene have been performed in two related consanguineous PCG affected families and four other sporadic Egyptian patients using the polymerase chain reaction (PCR) assay; where PCR products were sequenced, and further analyzed. Results: Sequencing analysis revealed three novel mutations in PCG affected patients one in the promoter region (g.G2872A) and two in exon1 (g.C3268T and g.C3332T). Two additional mutations in exon3 (p.L432V and p.N453S) are reported for the first time in PCG affected Egyptian patients. Clinical and genetic data of the two consanguineous families revealed that although the four parents have the same variations as their sons, they are ophthalmologically free. Regular ophthalmic examinations of siblings and parents of these affected patients should take place for early detection of any form of glaucoma to allow prompt diagnosis and early treatment when needed. Conclusion: The present investigation revealed the presence of six different mutations distributed on the promoter-exon1 region and the coding region of exon3 of CYP1B1 gene. To the best of our knowledge, three of these mutations are novel mutations reported for the first time in the present study. Clinical examination and molecular genetic data could contribute to early diagnosis and prevention of the visual impairment caused by PCG. This study provides groundwork for expanded genetic investigations in Egypt paving the way for genetic counseling to help affected families make informed medical and personal decisions.